Perception of the activities of Touts in Mushin and Oshodi Neighbourhoods (2011)
This study examines the activities of touts from the perceptions of Oshodi and Mushin residents and seeks to expose the factors necessitating the increasing involvement of youths in the obnoxious trade, as well as the security implication of touting in Lagos neighbourhood. A combination of quantitative and qualitative research methodology was adopted for this study. Major findings revealed touting as a survival strategy, linked to the rising level of unemployment, poverty, lack of education and parental care; and the perceived success of senior touts in the transportation corridors as motivating factors enhancing the activities of youths as touts in the two communities. Contrary to the researcher's expectations and major studies, residents highlighted the contributions of touts in neighbourhood security and crime control through the Odua People's Congress (OPC) and other local vigilante groups. A situation 65 percent of interviewed respondents attributed to the low crime rate in the two neighbourhoods. Based on these findings, the study recommends that governmental policies on employment should make provisions among others for unskilled, uneducated and energetic youths in urban development, as well as in neighbourhood security.